2022
DOI: 10.1007/s11255-022-03123-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends of primary glomerular disease in Turkey: TSN-GOLD registry report

Abstract: Background Although several renal biopsy registry reports have been published worldwide, there are no data on primary glomerular disease trends in Turkey. Methods Three thousand eight-hundred fifty-eight native kidney biopsy records were assessed in the Turkish Society of Nephrology Primary Glomerulopathy Working Group (TSN-GOLD) Registry. Secondary disease and transplant biopsies were not recorded in the registry. These records were divided into four periods, before 2009, 2009 to 2013, 2013-2017, and 2017-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This increase has been attributed to increased awareness of FSGS and an increase in the incidence of FSGS in the elderly secondary to diseases such as HT and agerelated nephropathy 30 . In studies conducted abroad, while MGN stands out as the most frequently detected PGN in Spain 37 , Czech Republic 11,24 , in our study, MGN (39.4%) was found to be the most common and FSGS (12.1%) was the second most common glomerular pathology, both among PGNs and among all patients who underwent biopsy. In terms of the frequency of PGN, the results of our study are similar to those reported by recent large-scale studies conducted in our country 11,26 .…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…This increase has been attributed to increased awareness of FSGS and an increase in the incidence of FSGS in the elderly secondary to diseases such as HT and agerelated nephropathy 30 . In studies conducted abroad, while MGN stands out as the most frequently detected PGN in Spain 37 , Czech Republic 11,24 , in our study, MGN (39.4%) was found to be the most common and FSGS (12.1%) was the second most common glomerular pathology, both among PGNs and among all patients who underwent biopsy. In terms of the frequency of PGN, the results of our study are similar to those reported by recent large-scale studies conducted in our country 11,26 .…”
Section: Discussionsupporting
confidence: 51%
“…Although biopsy indications vary on a national or center basis in the literature, it has been reported in many biopsy series that the most common indication in the elderly is nephrotic proteinuria 11,23,24,26,27 . In our study, nephrotic proteinuria (56.1%) was found to be the most common biopsy indication in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations